United States Dietary Trends Since 1800: Lack of Association Between Saturated Fatty Acid Consumption and Non-communicable Diseases - Lee, Joyce H.; Duster, Miranda; Roberts, Timothy; Devinsky, Orrin (Frontiers in Nutrition, 2022)
We reviewed data on the American diet from 1800 to 2019. Methods We examined food availability and estimated consumption data from 1808-2019 using historical sources from the federal government and additional public data sources. Results Processed and ultra-processed foods increased from <5% to >60% of foods. Large increases occurred for sugar, white and whole wheat flour, rice, poultry, eggs, and vegetable oils, dairy products, and fresh vegetables. Saturated fats from animal sources declined while polyunsaturated fats from vegetable oils rose. Noncommunicable diseases (NCDs) rose over the 20th century in parallel with increased consumption of processed foods, including sugar, refined flour and rice, and vegetable oils. Saturated fats from animal sources were inversely correlated with the prevalence of NCDs. Conclusions As observed from the food availability data, processed and ultra-processed foods dramatically increased over the past two centuries, especially sugar, white flour, white rice, vegetable oils and ready-to-eat meals. These changes paralleled the rising incidence of NCDs, while animal fat consumption was inversely correlated.